Sthreads: Multithreading for SCI clusters - Rehling, Enno (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
Threads are in widespread use as a model for concurrent programming. In our effort to supply a broad range of tools for the SCI platform, we have created Sthreads, a library that simplifies the adaptation of programs written for the Pthreads library to SCI Cluster hardware. This paper presents the design decisions we made, and a performance evaluation comparing the Sthreads library to Pthreads.